Determinants of Complete Basic Immunization in Babies Born in Period Covid 19 pandemic in West Java (2021 Susenas Data Analysis) - Naim, Salsabila (Varians Jurnal Kesehatan Masyarakat, 2023)
Since the Covid-19 pandemic, the implementation of basic childhood immunization services has decreased. In West Java, child immunization coverage decreased by 93.74% in 2019, to 82.26% in 2020. The aim of the study This is to find out the determinants of complete basic immunization in infants born during the COVID-19 pandemic in West Java. This study uses SUSENAS 2021 data in West Java with a sample of 368 infants aged 10-12 months who were born during the COVID-19 pandemic, with cross-sectional design and multiple logistic regression analysis. Factors related to complete basic immunization of 10-12 months babies born during the COVID-19 pandemic in West Java were the mother's last education, mother's employment status, economic status, ownership of health insurance, and ownership of MCH books. The most dominant factor is ownership of MCH handbook (p value = 0.00 ; AOR = 16,064 ; 95% CI = 6.397-40.339). Conclusion: The government can optimize the use of MCH books by developing the digitization of MCH books on a national scale. Puskesmas can work together with various parties, especially cadres in motivating families/communities to use and apply the contents of the MCH handbook